IMPLEMENTATION OF THE SELF REPORTING QUESTIONNAIRE (SRQ) SCREENING PROGRAM FOR NARCOTICS CONFIDENTS AT CLASS IIA NARCOTICS CORRECTION INSTITUTION IN JAKARTA - Ranisa Diati; Vivi Sylviani Biafri (Polteknik Ilmu Pemasyarakatan, 2022)
The screening program for early detection of psychiatric problems using the Self Reporting Questionnaire (SRQ) has the goal of developing mental health. The screening program for early detection of psychiatric problems using the Self Reporting Questionnaire (SRQ) held by the Class IIA Jakarta Narcotics Prison has not yet been carried out in other Correctional Technical Implementation Units (UPT), especially prisons and detention centers. The author is interested in researching this. The purpose of the study was to determine the implementation and obstacles to the Self Reporting Questionnaire (SRQ) screening program for narcotics prisoners at the Class IIA Narcotics Prison in Jakarta. The research method used is qualitative using a descriptive approach. The results showed that the implementation of the Self Reporting Questionnaire (SRQ) screening program for narcotics prisoners at the Class IIA Jakarta Narcotics Prison had not run optimally because in the management of the screening program there were still some shortcomings. The implementation of the Self Reporting Questionnaire (SRQ) screening program has several obstacles, namely: 1) lack of human resources, namely the screening officer, 2) the Self Reporting Questionnaire (SRQ) skinning program only focuses on prospective medical rehabilitation participants, 3) SRQ screening is not carried out continuously, 4) reporting of screening results has not been fully implemented and is constrained by the technical reporting flow. In optimizing the implementation of the Class IIA Jakarta Narcotics Prison, it is necessary to evaluate the Self Reporting Questionnaire (SRQ) screening program that has been running previously so that future plans can achieve the expected vision, one of which is that the implementation of SRQ screening is carried out for all prisoners, not only for prospective participants in medical rehabilitation and carried out continuously so that all prisoners have a healthy soul.